Stopping the Exploitation of Workers: An Analysis of the Effective Application of Consumer or Socio-Political Pressure - Pines, Gina L. S. (Journal of business ethics, 2005)
Commodity chain analysis (Bair and Ramsay, 2003 Multinational Companies and Global Human Resource Strategies) is used to explore where economic pressure (from consumers) or socio-political pressure (from governments and NGOs) can be applied to reduce worker exploitation. Six paths are illustrated with examples of successful and unsuccessful application of pressure. Three conclusions are reached :Economic pressure on companies and brand owners is more likely to lead to improved workplace conditions than socio-political pressure; Brand owners are more likely to implement improved workplace conditions than retailers; and Retailers who are under extreme consumer price pressure will resist improving workplace conditions.